EKSPERIMENTASI PEMBELAJARAN BAHASA ARAB BERBASIS SCRABBLE - Istiqomah, Istiqomah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
This Scrabble-based Arabic learning model basically is an attempt held by teacher in order that student can develop vocabulary, and having competence in active learning i.e. to learn to express himself both as individual or group. According to writer’s observation on Arabic learning in schools including MI Sultan Agung, the learning doesn’t make student as active learner yet. Furthermore, the teacher considers student as an object in teaching and learning process. It is expected from this Scrabble-based Arabic learning model that student can develop vocabulary competence more actively so that they can master Arabic both in spoken and written, and it also can be useful for his/her life in future.